UNDERPLATING AS A CAUSE OF THE VOLCANIC CONTINENTAL MARGIN FORMATION DURING MARGINAL SEA SPREADING - Filatova N.I. (My University, 2004)
Problems related to the rifting zones and continental margins of the opening sea basins include the necessity of explaining the alternation of active magmatic and a magmatic segments of continental margins recognized as volcanic and nonvolcanic passive continental margins.This phenomenon is inherent to not only global structures, such as the Atlantic Ocean, but also the marginal-sea basins (e.g., the Sea of Japan). The results of the study of the western framework of the Sea of Japan, petrologic investigations, ODP drilling, and seismic profiling have made it possible to elucidate the causes of the appearance of the depleted volcanics at the continental margin. These materials also revealed the genetic link of the volcanics with the deep structure of the continental margin and spreading of the adjacent sea basin.